Efficiency enhancement in dye-sensitized solar cells using silver nanoparticles and TiCl4. Issue 1 (2nd January 2017) - Kazmi, Safia A.; Hameed, Salman; Azam, Ameer
ABSTRACT: This paper reports the efficiency enhancement in dye-sensitized solar cells (DSSCs) by incorporation of silver nanoparticles (AgNPs) in Titanium dioxide (TiO2 ) and using it as anode. Further enhancement in DSSC parameters was observed after TiCl4 treatment on TiO2 Ag anode. It was observed that the short circuit current density J sc was increased from 6.95 to 12.58 mA/cm 2 by TiCl4 treatment with no change in V oc and fill factor increasing the efficiency from 3.29 to 5.61%. The fabricated DSSCs using TiO2 AgNPs anode with both pre and post TiCl4 treatment appear to have the maximum efficiency as compared to other cells. Due to effective electron transport and enhanced absorption of dye on TiO2 AgNPs anode surface, the maximum conversion efficiency of 7.3% was achieved.